Talleres de Dramatización para mejorar la comprensión de Textos Orales en Niños de 4 años del C.E.E. Rafael Narváez Cadenillas, 2016 - Leonardo Silva, Katia Jenifer (2017)
The development of this research work has been carried out based on the bibliographical references of authors and web pages consulted, as well as knowledge acquired during the academic years of our professional training._x000D_ The present research on "Dramatization workshops, to improve the understanding of Oral Texts in children of 4 years of C.E.E. Rafael Narváez Cadenillas, 2016 ", has as a primary purpose to address the problem that presents, most of the children of four years of C.E.E. Rafael Narváez Cadenillas that is difficult for the development of the comprehension of oral texts, which have an impact on the development of their learning._x000D_ The research is applicable and we used the quasi - experimental design of two groups: control group and experimental group, with pretest and posttest for both groups. This research was carried out in a sample of 40 children aged 4 years._x000D_ The results of the pretest show that the students of both sections (control and experimental) had difficulty in the development of the learning paths of the communication area, later of the application of the learning sessions for the experimental group, the results show an Increase meaning._x000D_ This research demonstrates that the application of learning sessions with methodological strategies can help improve the understanding of oral texts in children._x000D_ It is for this reason that we present this research based on methodological strategies to improve the understanding of oral texts in children of four years, taking into account the capabilities that provide us the learning paths 2015, which consists of 20 sessions, each session with didactic methods And novelties that will arouse the interest of the children which will allow a better learning.